Bonsái by Alejandro Zambra: An Elliptical and Autofictional Narrative - Jiménez Picado, Dahiana (2024)
The metafictional nature of the novel Bonsái (2006), by Chilean author Alejandro Zambra, has been extensively commented on by literary critics, in contrast to its autofictional aspects. By studying the figure of the narrator, the types of omissions present in the text, and diverse extraliterary elements that reveal the author’s poetic principles, this article demonstrates how the elliptical and autofictional narrative of the novel represents a departure from the realist literary tradition and questions the relationship between fiction and reality. Both of these literary devices—elision and autofiction—are constantly presented to the reader, who witnesses a process of open writing characterized by both the narrator’s (in)decisiveness and the reader’s interpretations that fill in the gaps in the text.